2017
DOI: 10.1002/cpp.2093
|View full text |Cite
|
Sign up to set email alerts
|

Sudden gains in exposure‐focused cognitive‐behavioral group therapy for panic disorder

Abstract: Sudden gains are common in panic disorder patients undergoing exposure-based cognitive-behavioral group therapy. Sudden gains during exposure-focused therapy are linked to greater improvement in panic disorder severity and functional impairment. The positive impact of sudden gains on panic disorder severity and functional impairment is maintained in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Nogueira-Arjona et al . (2017) also found sudden gains in patients receiving group CBT treatment for panic disorder and these were associated with lower levels of panic severity and functional impairment at the end of treatment and 6-month follow up.…”
Section: Introductionmentioning
confidence: 92%
“…Nogueira-Arjona et al . (2017) also found sudden gains in patients receiving group CBT treatment for panic disorder and these were associated with lower levels of panic severity and functional impairment at the end of treatment and 6-month follow up.…”
Section: Introductionmentioning
confidence: 92%
“…Individuals with combat-related trauma who had positive outcome in exposure showed a reduction in trauma-related guilt (Trachik et al, 2018). In addition, a general reduction in panic-related cognitions was observed in individuals who showed sudden gains in exposure treatment (Nogueira-Arjona et al, 2017), and changes in panic-related cognitions led to changes in the severity of panic symptoms (Hofmann et al, 2007). Other research has demonstrated that cognitions related to physical consequences of anxiety changed in the successful treatment of both agoraphobia and social anxiety (Vögele et al, 2010).…”
Section: Mechanisms Of Change Datamentioning
confidence: 99%